Kesesuaian Substansi Perda Rtrw Kabupaten di Provinsi Lampung - Abdullah, Mira Setiawati; Surjono, Surjono; Rachmawati, Turniningtyas Ayu (Fakultas Teknik, Universitas Brawijaya, 2012)
This paper begins with a mandate of law (UUPR 26/2007) on the approval of the technical substance by holding ministerial affairs in the field of spatial planning before the local draft regulation (raperda) on Spatial Planning (RTRW) set to local regulations (perda). The necessity was contained in the Ministry Law (Permen PU N0. 11/ 2009). This rule is a guideline in determining the substance of the agreement on draft of Regency Spatial Planning (RTRW-Kab/Kota) and Province Spatial Planning (RTRWP). Conformity substance intended for government regulation of National Spatial Planning (PP RTRWN), local regulation (perda) RTRWP and perda RTRW-Kab/Kota established in accordance with the technical rules of the field of spatial planning to realize an integrated spatial plans and complementary to the spatial hierarchy of planning. The purpose of this research is to measure the level of substance compliance of perda RTRW-Kab againts perda RTRWP Lampung, PP RTRWN and Permen PU No.11/2009. Overall, the analysis was performed by using the comparative method, comparing substance of perda RTRW-Kab with the substance contained in perda RTRWP Lampung, and PP RTRWN as well as to compare the content of perda RTRW-Kab fit in writing systematic of Permen PU No.11/2009 to find conformity-nonconformity. The analysis technique used is content analysis or study of the content. The study shows that the level of perda RTRW-Kab conformity in Lampung province average is very high at 92.1%. Conformity with the substance of perda RTRWP Lampung and PP RTRWN is 92%, and the content according Permen PU No.11/2009 is 93%..Keywords: Level of conformity, Substance, Regency Spatial Planning.